Analysis of Consumption Behaviour of Millennial Housewives: A Case Study in Pacitan Based on Al-Ghazali's Consumption Theory - Alam, Azhar; Purwaningsih, Rista; Isman, Isman (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2023)
Consumption behaviour is part of human life's needs, which are also regulated in Islam. However, the phenomenon of the emergence of Islamic economics has not completely changed people's consumption behaviour to be more in line with Islamic teachings. This research aims to determine the consumption behaviour of millennial homemakers in Pacitan and its suitability in terms of Al-Ghazali's consumption theory. This study used a case study in Pacitan by interviewing 20 informants in depth from various literature related to consumption behaviour in Islam. The research results show that their consumption behaviour always prioritizes fulfilling primary needs in the form of food, shelter, clothing, education and health. When faced with a choice between needs and desires, desires will be fulfilled after primary needs are met. Apart from that, they also always use halal assets and goods and make plans to save for their children's education costs or if there is a sudden need. However, a group of millennial housewives are still wasteful and stingy and have not paid zakat and alms as a form of concern for the surrounding environment. This research is an initial study revealing the study of people's consumption behaviour based on Islamic economic thinkers. The study can be a reference for studying Islamic consumption behaviour for academics and improving people's consumption behaviour.